Atividade in vitro do danofloxacin e de sete drogas antimicrobianas frente a linhagens de Staphylococcus aureus de mastite bovina - Cruz, A. D.; Batista, GCM; Modolo, JR; Gottschalk, A. F.; Lopes, CAM (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1998)
The antimicrobial activity, of danofloxacin, a new 4-fluoroquinolone for exclusive use in Veterinary Medicine, was compared in vitro with other seven drugs against 200 strains of Staphylococcus aureus isolated from bovine mastitis. By using the antimicrobial disk diffusion method (Bauer-Kirby), the results showed that the imipenem (100%), trimerhoprim/sulfamethoxazole (98.9%), cefuroxime (97.3%) were the most effective drugs taking into consideration the percentuals of sensitiveness. However, considering the percentuals of the moderately sensitive strains, danofloxacin emerged as the third most active drug. The antimicrobial dilution susceptibility test used to study the minimal inhibitory concentration (MIC) and the minimal bactericidal concentration (MBC) of danofloxacin, characterized its significative antimicrobial activity by showing a close relationship between both concentrations (MIC90%= 18 mu g/ml - MBC90% = 0.23 mu g/ml), as well as a MIC/MBC ratio of 1:1 and 1:2 for most of tested strains.
Antimicrobial activity of danofloxacin and seven other drugs against Staphylococcus aureus from bovine mastitis
Keywords: bovine; Staphylococcus aureus; mastitis; danofloxacin